Effects of drying rate and storage time on Magnolia ovata Spreng. seed viability - José, A. C.; Silva, Edvaldo Aparecido Amaral da [UNESP][; Davide, A. C.; Melo, A. J S; Toorop, P. E. (My University, 2011)
Magnolia ovata seeds have been reported as desiccation sensitive. In order to test if the drying rate would affect the assessment of storage behaviour of these seeds, the effect of different drying rates and storage times on the viability was tested. Seeds were dried over activated silica gel (fast drying) or salt solutions for different periods (slow drying) and stored at -20°C. Partial drying transiently increased the final germination and the germination speed index, but further drying resulted in reduction of these parameters. Drying rate affected the final germination and vigour. Seeds that were slow-dried to 0.10 g H 2O ̇ g -1 dw retained high viability when compared with seeds desiccated to the same water content level by the fast drying method, although their vigour was reduced. Only slow-dried seeds could be stored at -20°C for 90 d without reduction of viability. These data suggested that the storage behaviour of seeds of M. ovata seeds should be classified as intermediate.
Keywords: Magnolia ovata; Magnoliaceae